Acid(g)/base(g)-controlled reversible Δν1/2 of absorption spectrum of a functional dye film - Noh, Ha Lim; Oh, Byeong M.; Baek, Seungmin; Park, Sung Ha; Jeon, Gyeong G.; Yoon, Sang Eun; Zheng, Jian; Kwon, O. Pil; Kim, Sang Wook; Kim, Jong H. (Dyes and Pigments, 2020)
UV–Vis absorption full width at half maximum (FWHM) plays a significant role not only in describing spectral shapes but also in determining the use of organic dyes for a particular application. For example, organic dyes with a relatively wide absorption FWHM are beneficial with respect to enhancing photon absorption efficiency of solar cells, whereas, for improving color purity in optical filters, narrow FWHM is desirable. Despite such a critical role, studies examining the modulation of absorption FWHM from an organic dye in the solid state are relatively lacking. In this work, we suggest rapid, simple, and effective method to control the absorption FWHM of a squarylium-based dye (SQ) film using an organic solvent vapor. Alternative treatments of base/acid gas to the SQ film (2.0 s for each gas) resulted in reversible absorption FWHM (ΔFWHM: 121 nm). From the systematic optical and morphology characterizations, it was revealed that changes in FWHM originated from reversible molecular arrangements between monomer-type and H-aggregate-type of SQ by efficient base/acid vapor diffusion into the SQ film. Moreover, the modulation exhibited high fatigue resistance against repeated gas treatments, which secures its practical applications. These results suggest that the proposed simple gas-treatment process in this work is beneficial for the efficient modulation of absorption FWHM of various organic dyes.
Keywords: Gas treatment; Molecular arrangements; Morphology characterizations; Organic solvent vapors; Photon absorptions; Spectral shapes; Vapor diffusion; Vis absorption; Absorption spectrum; Aggregation; Full width at half maximum; Gas treatment; Monomer; Organic dyes